Further evidence of the association between LQT syndrome and epilepsy in a family with KCNQ1 pathogenic variant. (February 2015) - de Llano, Coloma Tiron; Campuzano, Oscar; Pérez-Serra, Alexandra; Mademont, Irene; Coll, Monica; Allegue, Catarina; Iglesias, Anna; Partemi, Sara; Striano, Pasquale; Oliva, Antonio; Brugada, Ramon
Highlights: Presence of sudden cardiac death in patients with epilepsy is common. KCNQ1 _p.L273F causes familial epilepsy and long QT syndrome. KCNQ1 confer susceptibility for recurrent seizure, increasing the sudden death risk. Abstract: Purpose: Ion channels are expressed both in the heart and in the brain, being advocated as responsible for sudden unexpected death in epilepsy but few pathogenic mutations have been identified. We aim to identify a novel gen associated with channelopathies and epilepsy in a family. Methods: We assessed a family showing epilepsy concomitant with LQTS. Index case showed prolonged QT interval. His father suffers of LQT and epilepsy. We performed a direct sequencing analysis of KCNQ1, KCNH2, KCNE1, KCNE2 and SCN5A genes. Results: We identified a non-synonymous heterozygous missense pathogenic mutation (p.L273F) in exon 6 of the KCNQ1 gene. All clinically affected relatives carried the same mutation. Conclusion: We report, for a first time, a KCNQ1 mutation in a family suffering of both phenotypes, suggesting that KCNQ1 genetic variations may confer susceptibility for recurrent seizure activity increasing the risk or lead to sudden death.